1987
DOI: 10.1289/ehp.8776221
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence among welders: possible effects of exposure to extremely low frequency electromagnetic radiation (ELF) and to welding fumes.

Abstract: Epidemiological studies of cancer incidence among welders disclose a pooled total of 146 cases of leukemia observed versus 159.46 expected, a risk ratio of 0.92, and 40 cases of acute leukemia observed versus 43.39 expected, a risk ratio of 0.92. For respiratory tract cancer, the pooled total is 1789 cases observed versus 1290.7 expected, a risk ratio of 1.39. Most electric welders are exposed to extremely low frequency electromagnetic radiation (ELF) (magnetic flux densities of up to 100,000 microT), a suspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 51 publications
2
4
0
Order By: Relevance
“…They support previous study findings suggesting an association between lung cancer and exposure to asbestos or PAH among these workers [Ronco et al, 1998;van Wijngaarden et al, 2001;Meguellati-Hakkas et al, 2006]. Other work associated with exposure to asbestos and PAH, particularly welding [Stern, 1987;Siemiatycki, 1991;Ronco et al, 1998], but also computer services, telecommunication equipment, radio, and television broadcasting equipment operators, and motion picture, audio and video production were at increased risk in our study. Conversely, a study of male employees at five electrical utility companies found only weak associations with lung cancer, and risk was not influenced by duration of work [Savitz et al, 1997].…”
Section: Discussionsupporting
confidence: 92%
“…They support previous study findings suggesting an association between lung cancer and exposure to asbestos or PAH among these workers [Ronco et al, 1998;van Wijngaarden et al, 2001;Meguellati-Hakkas et al, 2006]. Other work associated with exposure to asbestos and PAH, particularly welding [Stern, 1987;Siemiatycki, 1991;Ronco et al, 1998], but also computer services, telecommunication equipment, radio, and television broadcasting equipment operators, and motion picture, audio and video production were at increased risk in our study. Conversely, a study of male employees at five electrical utility companies found only weak associations with lung cancer, and risk was not influenced by duration of work [Savitz et al, 1997].…”
Section: Discussionsupporting
confidence: 92%
“…In a survey of ELF-MF around almost different ELF-MF household appliances, weak levels from 0.03 to 2.9 μT were measured in a typical user distance (Delpizzo 1990). However, the ELF-MF generating from transmission lines, transportation and industrial work-place was strong up to 0.1-50 mT (Stern 1987). The strength of ELF-MF we exposed to animals in this study was comparable to the occupational exposure predominant from working near industrial equipment using high currents.…”
supporting
confidence: 53%
“…Special attention has been given to occupations involving welding because of the relative intensity of EMF exposure that such workers may experience. Despite such exposure, evidence of any increased cancer risk is weak, if not negative 29 …”
Section: Occupational Studiesmentioning
confidence: 99%
“…Half have been from the United States, 32 , 36 , 37 , 39 , 42 44 one from France, 24 one from France and Canada, 41 and the remainder from Scandinavian countries 31 , 33 , 35 , 38 , 40 . Nine studied a variety of job categories associated with EMF exposure, 31 35 , 38 , 39 , 42 , 43 three studied workers at electric utilities, 37 , 41 , 44 and one each studied telephone linemen 36 and railway workers 40 . EMF exposure was judged at least partially in seven studies by measuring field strengths in the workplace 35 37 , 39–41 , 44 and by coding job descriptions in the remainder.…”
Section: Occupational Studiesmentioning
confidence: 99%